POLA KOMUNIKASI PADA KALANGAN LESBIAN DALAM PENGEMBANGAN HUBUNGAN ANTAR PRIBADI (STUDI PADA KOMUNITAS SRIKANDI DEWATA) - Agestiary Saputri, Ni Kadek; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2017)
The goal of this research is to know the communication pattern used by lesbians in the Srikandi Dewata Community in the process of developing interpersonal relationship up to the stage of intimacy to be a lover. This research uses descriptive qualitative type. Informants were selected by purposive and snowball techniques. Data were obtained by using in-depth interview technique, direct observation, and documentation study. Data analysis techniques used in this study through several stages namely, data reduction, data presentation, and conclusions. The results showed that lesbians within the Srikandi Dewata Community used four patterns of communication in the process of developing relationships to the stage of intimacy to become lovers. First is the primary communication pattern in which they use verbal and non verbal communication in the development of their relationship. Second is the pattern of secondary communication, they use the second channel or media in the delivery of messages, namely mobile and use of chat applications. Third is a linear communication pattern, this communication pattern is formed from the stages and process of developing their interpersonal relationship, from interpersonal communication stage, contact stage, stage of engagement, and stage of intimacy. Fourth is the circular communication pattern, this pattern is used in the stage of involvement and stage of familiarity to know the respond an feedback from the message given from the communication to the communicator.   Keywords : Communication Pattern, Relationship Development, Lesbian, Lesbian Community